Cuerpos travestis en los discursos ficcionales latinoamericanos - Bianchi, Paula Daniela (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2008)
The core of this paper addresses the representation of transvestite and destabilizing bodies in Latin American literature from the nineties onwards: that is, the articulation of these bodies and fictions as a device to produce sense and political, social, cultural and discursive representations, as for example in the novels Salón de belleza [Mario Bellatin], Sirena Selena vestida de pena [Mayra Santos Febres], El rey de la Habana [Pedro Juan Gutiérrez] or Tengo miedo torero [Pedro Lemebel], among others. This does not imply ascribing literature a realist status -as a reflection of the social reality-, but exploring the ways of this construction which coexist, either by complementing or disintegrating themselves from the widest social and cultural models circulating within society